Pengaruh Variasi Crude Oil Yang Diolah Terhadap Nilai Konversi Produk Green Cokedi PT Pertamina RU II Dumai - Muhammd Ichsan; Syarfi Daud; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pertamina Dumai Refinery has carried out Open Access Project which changed the processed crude from initial design by substituting SLC with another "light sweet" crude from outside Riau. The percentage of this replacement reaches 50% of the total crude intake. This study reviews the impact of changes in the composition of processed crude oil on the composition of produced green coke. The research was conducted throughout 2018 with preliminary data gathered since 1996. Green coke samples were taken per month for properties analysis such as moisture content, volatile matters, ash content, sulfur content and fixed carbon, to calculate conversion value of green coke. The conclusion of this research is that the fluctuations in the crude composition were quite significant towards the composition and the conversion value (ton to barrel) of the produced green coke.Keywords: crude oil, conversion, green coke, volatile matter